Comparing the Voice Handicap Index Scores in Groups with Structural and Functional Voice Disorders - Marzieh Jalalian (Journal of Rehabilitation, 2019)
Objective: The effects of voice disorders vary from person to person. Occupation, work environment, life, and family reaction are variables that affect one’s perception of his/her own as an impaired voice. Voice Handicap Index (VHI) has not yet been used to compare the degree of voice disorders. Assuming that the quality of life may be different under a variety of voice disorders and that different physical, emotional and functional aspects maybe affected differently and that each disorder has a different treatment, This stud was conducted to prioritize and propose the appropriate treatments (voice health, manual therapy of larynx, voice therapy, and referral to relevant specialists) based on VHI score. Materials & Methods: This is a descriptive/analytic study with cross-sectional design. Firstly, voice disorder of 166 patients aged 18-60 years referred to private clinics in Tabriz city was confirmed based on the diagnosis of a otolaryngologist and laryngeal stroboscopic images. VHI test was performed and a questionnaire was used to survey them in the presence of examiner to answer their potential questions. The VHI test consists of 30 items and 3 subscales of physical (10 items), emotional (10 items) and functional (10 items) rated on a 5-point Likert scale (0=Never, 1=Almost Never, 2=Sometimes, 3=Almost Always, and 4=Always). The patient's stroboscopic samples was examined by 3 speech-language pathologists and based on their consensus, patients were assigned into functional and structural voice disorders. In the next step, values obtained from the VHI test were compared between the two groups based on three subscales. Finally, the data were analyzed in SPSS v.19 software using statistical methods such as mean, standard deviation and Multivariate Analysis Of Variance (MANOVA). Results: The rate of voice impairment was significantly higher in patients with structural voice disorder than in patients with functional disorder in overall and based on functional, physical and emotional components (p<0.05). Based on Kolmogorov-Smirnov test results, the variables had normal distribution. According to the Box test results, the studied groups were homogeneous in terms of study variables. Based on Bartlett's test of sphericity results, the assumption of correlation between the variables was established, since the mean value of patients in the structural group was significantly higher than in the functional group (P<0.05). the mean scores of individuals with structural voice disorders in physical (18.7) and emotional (15.2) dimensions were significantly higher than in those with functional voice disorders (P<0.05). Conclusion: Voice impairment in the structural group was lower than in the functional group. A comprehensive treatment should be considered for patients with structural voice disorder with an emphasis on improving the psychological aspects of voice disorders.